KEBIJAKAN VALUASI ASET KOLEKSI ILMIAHUNTUK MEWUJUDKAN PENGELOLAAN BARANG MILIK NEGARA YANG AKUNTABEL DAN PRODUKTIF DALAM MENDUKUNG RISET DAN INOVASI DI LINGKUNGAN BADAN RISET DAN INOVASI NASIONAL - Achmad Chodiq (Jurnal Salome : Multidisipliner Keilmuan, 2024)
This study aims to conduct analysis and study as a scientific basis for the preparation of the draft Valuation Guidelines for scientific collection assets in the form of Biological Assets including: Plants, animals and Historical Assets including: manuscripts, artifacts and languages with accounting purposes, which provide direction, and determine the scope in the preparation of Technical Guidelines for Valuation of scientific collection assets In the National Research and Innovation Agency, it is further expected to realize the strengthening of accountable, productive BMN management, compliance in the management of State Property to laws and regulations and efficient in supervision and control and the implementation of reliable BMN administration. Data Collection Techniques used in this study are through literature research/review (library research) to obtain theoretical concepts, opinions or conceptual thoughts related to the object of this research study, which can be in the form of laws and regulations and other scientific works. The method used is a systematic and interdisciplinary scientific study through literature reviews, a series of discussion activities, studies through media, analysis and evaluation, and preparation of manuscripts. The results of the research in the preparation of the Academic Manuscript on the Valuation Policy of Scientific Collection Assets are intended as a reference, referral and guideline on the Management of Property in the form of Scientific Collection Assets in the BRIN Environment, so that it can be implemented more orderly administratively in the management of BMN in question. Furthermore, asset management must also be based on compliance with policies and regulations and adherence to principles that completely cover important aspects of BMN management, but still provide opportunities for creativity, innovation and collaboration in order to find the most appropriate and appropriate pattern with the current dynamics of the organization, so that the strategic role mandated through the Presidential Instruction of the Republic of Indonesia, Number 1 of 2023 concerning Mainstreaming Biodiversity Conservation in Sustainable Development to BRIN and the Decree of the Minister of Finance of the Republic of Indonesia Number 112/Km.6/2024 concerning Performance Indicators for Management of State Property in 2024. one of which is in the Management of Scientific Collection Assets from Research Results so that it can be implemented properly.